Walk 3 WAR AND PEACE - -, - (project baikal, 2011)
Memorial Complex «Tank “Irkutsky Komsomolets”»V.P.Sukhachev’s Estate ParkSketch of Development along Dekabrskikh Sobyty Street and Ushakovka-Angara Green AxeTrade Unions ‘ Recreation Center for 800 seats on Dekabrskikh Sobyty Street1200-seat Hostel for Institute of National Economy on Sovetskaya StreetMonument to Irkutsk Citizens Killed on Military Duty